Penatalaksanaan gingival enlargement gigi geraham pada penderita hipertensi terkontrol - Putranto, Ricky Anggara; Aisah Afinsaputri, Syafira; Alice, Vincentia (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Gingival enlargement is characterized by an abnormal increase of gingival tissue, often leading to cosmetic issues and difficulties in maintaining oral hygiene due to plaque accumulation. Gingivectomy, a surgical procedure to remove excessive gingival tissue, is frequently employed to restore healthy, functional, and aesthetically pleasing gingiva. This case report describes the gingivectomy technique using a scalpel as a treatment for gingival enlargement. Case report: A 52-years-old woman reported swelling in the upper left posterior gingiva, which bled easily during toothbrushing. She had a history of hypertension. Examination revealed gingival overgrowth that covers up half of the crown of teeth 26 and 27. Treatment began with initial non-surgical care, followed by evaluation and surgical intervention using a scalpel to remove the excess tissue. The surgical site was cleaned with hydrogen peroxide (H2O2) and povidone-iodine, and the root surfaces were smoothed. The patient received post-surgical care instructions and periodontal maintenance education. A follow-up after three weeks revealed no complaints from the patient, no signs of inflammation and no recurrence of gingival enlargement. Conclusion: Gingivectomy proved to be an effective approach for treating gingival enlargement in patient with hypertension, successfully restoring gingival health and function.